1997
DOI: 10.1021/ja971083v
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption Induced by Kiloelectronvolt Ion Bombardment of Thiol-Bound Self-Assembled Monolayers on Gold

Abstract: Time distributions of neutral molecules desorbed from a chemisorbed self-assembled monolayer of phenylethanethiol on gold have been measured subsequent to 8 keV Ar + and H 2 + ion bombardment. These distributions show that, regardless of the projectile used, most of the ejected molecules leave the surface with thermal kinetic energies (∼0.03 eV). The shapes of the distributions have a strong surface temperature dependence over the range 240-300 K. This behavior is well described by a convolution of the Maxwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
0
47
0
1
Order By: Relevance
“…36,37 The discovery of ion/ surface reactions that are sensitive to closely related chemical species should make it possible to extend the scope of this methodology for adsorbate characterization. The fact that ion/ surface inelastic processes can provide data even for fractional monolayer coverages should increase the potential value of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The discovery of ion/ surface reactions that are sensitive to closely related chemical species should make it possible to extend the scope of this methodology for adsorbate characterization. The fact that ion/ surface inelastic processes can provide data even for fractional monolayer coverages should increase the potential value of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minor fraction of emitted molecules has higher kinetic energies. A careful analysis using dierent projectiles showed that these molecules are sputtered with kinetic energies of the order of 1 eV by a direct momentum transfer from the incident ion to the gold substrate and ®nally to the organic layer [7].…”
Section: Resultsmentioning
confidence: 99%
“…We have postulated that low energy emission of PEM fragments can be explained by chemical reactions stimulated by the primary ions [7]. Direct bond scission by projectile impact can be excluded since it would cause the molecules to eject with high kinetic energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The velocity distributions follow Maxwellian behavior with a temperature that closely track the substrate temperature. 47 For solid organic materials such as tryptophan though most molecules eject due to a ballistic process, emission of molecules for long times after ion impact is observed. 48 These data suggest that long-lived excited states may be involved in the desorption event.…”
Section: Resultsmentioning
confidence: 99%